Perceptions and preparedness of secondary teacher trainees to foster inclusive schools for all - Arias-Pastor, Mercedes; Van Vaerenbergh, Steven; Fernández-Solana, Jessica; González-Bernal, Jerónimo J. (Frontiers in Education, 2023)
The development of inclusive education in recent decades emphasizes the pivotal role of teachers in transforming the educational landscape. As schools transition towards a more inclusive approach, it is imperative to evaluate the efficacy of initial teacher training programs in preparing educators for this inclusive transition. This study aims to describe the preparedness and perceptions of students in the Master's Degree in Secondary Education, Vocational Training, and Language Teaching (MDSE) regarding inclusive education, guided by the profile developed by the European Agency for the Development of Special Needs and Inclusive Education (AEDNEEI). Furthermore, the research analyzes how ex-ternal factors, such as perceived self-efficacy, influence these perceptions and readiness for inclusive teaching. A total of 218 students enrolled in the MDSE, with an average age of 31.5 years and a standard deviation of 6, were examined. Of the participants, 33% were male and 67% were female. These students came from different Spanish universities and were either in the final stages of their studies or had already completed them. Prior to participating, they had finished the generic module and completed their practice sessions in secondary education centers. The "Teacher Training in Secondary Education: Key Elements for Teaching in an Inclusive School for All" (TTSE-IN) questionnaire was employed, which includes five validated and relevant instruments, of which four were used for the study's purpose: The (Questionnaire for Future Secondary Education Teachers about Perceptions of Diversity Attention, the Questionnaire for the Evaluation of Teacher Training for Inclusion (CEFI-R), the Scale of Feelings, Attitudes, and Concerns about Inclusive Education, (Revised SACIE-R), and the Brief Scale of Teacher Self-Efficacy). The results show the presence of positive attitudes in future educators along with a poor overall assessment of the training received, which raises concerns about the development of teaching functions more related to daily work in the classroom and the implementation of inclusive methodologies. At the same time, both regular and close contact with people in situations of special vulnerability, experience in training in nonformal contexts,